SYNTHESIS, CHARACTERIZATION, AND ANTHELMINTIC ACTIVITY OF NOVEL BENZOTHIAZOLE DERIVATIVES CONTAINING INDOLE MOIETIES - RAJAREDDY, ALETI; MURTHY M, SRINIVAS (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this study was to synthesize and evaluate the anthelmintic activity (AA) of novel benzothiazole derivatives containing indole moieties (BDIM). Methods: The present works which involve the substituted isatin Schiff bases undergo acetylating and reacting with 2-aminobenzothiazole to give novel BDIM. Results: All the newly synthesized molecules (5a-5o) were characterized by Fourier-transform infrared spectroscopy, H_nuclear magnetic resonance, and mass spectral analysis along with physical data. The biological potentials of the newly synthesized compounds are evaluated for their AA using an Indian earthworm (Pheretima posthuma), and albendazole was used as standard drug. Conclusion: The synthesized compound 5f, 5n, and 5o showed good AA, whereas others exhibited significant activities.